Application of tableau de bord in the key accounts department of a fuel trading company: The case of PRIO supply - Rodrigues. M.; Nunes, R.; Trigo, A. (New Perspectives and Paradigms in Applied Economics and Business. ICAEB 2023. Springer Proceedings in Business and Economics, 2024)
Key Accounts Managers are responsible in an organization for the management of large clients requiring Management Information Systems that provide them in real time accurate and timely information for decision making. This project arises, therefore, as a response to this need and its main objective is to provide the Key Accounts Managers of a fuel trading company with an effective management control tool, having been chosen the Tableau de Bord. As contributions of this project to the academic and practical community we have the systematization of Key Performance Indicators for the Key Accounts Department using the OVAR (Objectifs-Variables d’Action-Responsables) method and their availability in dashboards that constitute the Tableau de Bord.